Early Music - Stevens, Denis 1922-2004 (London Kahn & Averill, 1987)
Although 'Early Music' as a term of reference has now replaced 'ancient', 'old', or 'pre-classical', performance issues remain much the same as before. This book offers fresh solutions for singers, players and directors.